Legal Barriers in the System of University Inclusive Education - A. E. Balashov; E. A. Krasnova; L. V. Khristoforova (Russian State Vocational Pedagogical University, 2020)
Introduction. The introduction of inclusive education into the practice of university education is a complicated and multi-aspect process accompanied by a complex of problems, including the problems of a legal nature. The solution of these problems is one of key tasks faced by the education system of Russia.The aim of the present research is to reveal and describe normative and legal barriers in the system of inclusive higher education, withdrawing the equal rights for education for all students regardless of their physical status and health.Methodology and research methods. The methods involve the analysis of legal and regulatory acts, regulating the orders and conditions of inclusive education at higher school. Russian and foreign literature on different aspects of inclusive education in higher school was reviewed, generalised and sistematised. The modelling method was employed.Results. On the basis of the existing legal norms, the reflection of the analysed materials made it possible to model the system of interaction between the participants of inclusive educational process - people with disabilities (HIA) and educational organisations. The constructed "theoretical" model allowed the authors to diagnose inclusion in higher education and to identify weaknesses in the provisions, which regulate the education of people with disabilities. Certain contradictions were found in the legal field of relations between these categories of students and educational institutions. The attention is drawn to the fact that in today's Russia the system of spesialised support for universities and for students with special needs is being formed, including resource training centres. However, these structures need to determine their place and status in the field of educational rights.Scientific novelty. The authors firstly formulate the legal barriers, impeding the continuity of psychological medico-pedagogical support for students with disabilities. The conclusion is reached concerning the signs of discrimination in the rights of students with special educational needs and the urgent need for improved higher inclusive education, including the optimisation at the level of legislative regulation.Practical significance. The authors believe that introduction of changes into normative regulations with the purpose to provide equal rights and opportunities for receiving education by all citizens will contribute to more dynamic and orderly development of university inclusion in Russia and will help people with health disabilities to become full members of society.